A robust and healable polyurethane based on coordination bonds. Issue 9 (18th May 2020) - Xu, Shaobin; Sheng, Dekun; Zhou, Yan; Wu, Haohao; Xie, Haopu; Liu, Xiangdong; Yang, Yuming
Abstract: Most self‐healing materials based on noncovalent bonding suffer from poor mechanical performance, which largely limits their further application. Herein, we designed and synthesized robust and healable polymers that can be healed under heating. They consist of a linear and three‐arm branched polyurethane mixture with triazole ligand end groups that are noncovalently linked through Fe–triazole interaction. The three‐arm branched polyurethane in the polymer mixture would imply parts of Fe‐triazole coordination bonds were replaced by covalent bonds and, as a consequence, yield materials with improved mechanical properties. Additionally, the mechanical properties of resulting polymers can be tuned by the number of Fe–triazole supramolecular crosslinks. Due to the dynamic nature of Fe–triazole interaction, all the metallopolymers exhibit excellent healable efficiency (over 90%) based on toughness. © 2020 Society of Chemical Industry Abstract : Introducing coordination bonding into a linear and three‐arm branched polyurethane mixture with triazole ligand end groups resulted in a polymer with improved mechanical properties and excellent self‐healing ability.